2016
DOI: 10.1037/xap0000074
|View full text |Cite
|
Sign up to set email alerts
|

Evidence accumulation in a complex task: Making choices about concurrent multiattribute stimuli under time pressure.

Abstract: Evidence accumulation models transform observed choices and associated response times into psychologically meaningful constructs such as the strength of evidence and the degree of caution. Standard versions of these models were developed for rapid (∼1 s) choices about simple stimuli, and have recently been elaborated to some degree to address more complex stimuli and response methods. However, these elaborations can be difficult to use with designs and measurements typically encountered in complex applied sett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
62
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(71 citation statements)
references
References 44 publications
7
62
2
Order By: Relevance
“…Our manipulation of the number of stimuli, although analogous to Palada et al (2016), used trials with a predetermined number of ships, rather than a probabilistic manipulation to draw the number of ships presented in a 3-minute period. Regardless of this difference, like Palada et al (2016), we found that participants did not respond to the number of stimuli by changing their rate of information processing. Rather, the number of stimuli selectively influenced threshold; participants strategically lowered their threshold when more ships were present, prioritizing the speed over the accuracy of their choices to reduce non-responses.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our manipulation of the number of stimuli, although analogous to Palada et al (2016), used trials with a predetermined number of ships, rather than a probabilistic manipulation to draw the number of ships presented in a 3-minute period. Regardless of this difference, like Palada et al (2016), we found that participants did not respond to the number of stimuli by changing their rate of information processing. Rather, the number of stimuli selectively influenced threshold; participants strategically lowered their threshold when more ships were present, prioritizing the speed over the accuracy of their choices to reduce non-responses.…”
Section: Discussionmentioning
confidence: 99%
“…They also observed that non-decision time decreased when participants had tighter deadlines. Palada et al (2016) extended this approach to a more complex task, testing whether the LBA was capable of accounting for performance on a simulation involving a navigation and target classification task that is more representative of the types of tasks found in applied settings. They found that the LBA was able to provide an accurate characterization of all aspects of performance even though multiple stimuli were simultaneously present in the display, and participants were free to decide how they allocated their attention amongst tasks and stimuli.…”
Section: Linear Ballistic Accumulator Modelmentioning
confidence: 99%
See 3 more Smart Citations